2004
DOI: 10.1603/0022-2585-41.3.414
|View full text |Cite
|
Sign up to set email alerts
|

Field Evaluation of Repellent Formulations Containing Deet and Picaridin Against Mosquitoes in Northern Territory, Australia

Abstract: Field efficacy of repellent formulations containing picaridin (1-methyl-propyl 2-(2-hydroxyethyl)-1-piperidinecarboxylate) or deet (N,N,-diethyl-3-methylbenzamide) against mosquitoes in Northern Territory, Australia, was evaluated. The following repellent treatments were evaluated: 19.2% picaridin (Autan Repel Army 20), a solution of 20% deet in ethanol, and 35% deet in a gel (Australian Defense Force [ADF]). The predominant mosquito species were Culex annulirostris Skuse (57.8%), Anopheles merankensis Venhuis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 8 publications
4
34
0
Order By: Relevance
“…The specificity of repellency still needs to be determined, but it is likely to be broad acting. Many synthesized repellents such as DEET, and naturally occurring ones such as azadirachtin (neem tree extract) have repellent and/or anti-feedant action against a diversity of insect types, including mosquitoes (Ravindran et al 2002;Frances et al 2004;Hou et al 2004). The demonstration of blowfly anti-feedant properties in L. caerulea skin secretion (Williams et al 1998), which is also active against mosquitoes, supports such an hypothesis.…”
Section: Discussionmentioning
confidence: 98%
“…The specificity of repellency still needs to be determined, but it is likely to be broad acting. Many synthesized repellents such as DEET, and naturally occurring ones such as azadirachtin (neem tree extract) have repellent and/or anti-feedant action against a diversity of insect types, including mosquitoes (Ravindran et al 2002;Frances et al 2004;Hou et al 2004). The demonstration of blowfly anti-feedant properties in L. caerulea skin secretion (Williams et al 1998), which is also active against mosquitoes, supports such an hypothesis.…”
Section: Discussionmentioning
confidence: 98%
“…Despite the proven efficacy of DEET as a repellent, during laboratory and field trials it is common to find that a small proportion of mosquitoes are not repelled by the compound (13)(14)(15). Boeckh et al (4) demonstrated that DEET reduced, but did not entirely eliminate, the approach of A. aegypti to host odors, and experiments with Drosophila melanogaster (16,17) and A. aegypti (18) have shown the presence of DEET-insensitive individuals.…”
mentioning
confidence: 99%
“…There is a considerable body of scientific work supporting their safety and effectiveness 7,9 , with laboratory and field investigations demonstrating that DEET effectively protects against a range of nuisance-biting and vector mosquito species in Australia. 10 …”
Section: Diethyltoluamide (Deet)mentioning
confidence: 99%
“…9,10 Registered formulations range in concentration from 9% to 20%. Alongside DEET, it has been widely recommended by health authorities internationally.…”
Section: Picaridinmentioning
confidence: 99%